Cooperative reduction of various RAFT polymer terminals using hydrosilane and thiol via polarity reversal catalysis. Issue 37 (2nd April 2019) - Uchiyama, Mineto; Satoh, Kotaro; Kamigaito, Masami
Abstract : Cooperative reduction of various thiocarbonylthio polymer terminals was investigated using thiol as a polarity reversal catalyst with hydrosilane as a reducing agent. Abstract : Cooperative reduction of thiocarbonylthio terminals of polymers obtained by RAFT polymerization was investigated using a catalytic amount of thiol as a polarity reversal catalyst in conjunction with hydrosilane as a reducing agent. A combination of C12 H25 SH and Ph3 SiH enabled the complete removal of xanthate, dithiobenzoate, and trithiocarbonate groups from poly(vinyl acetate), polystyrene, and poly(methyl acrylate) under the radical conditions.